Penggunaan Strength untuk Meningkatkan Engagement dan Kinerja Karyawan - Pratiwi, Pundani Eki; Asih, Gusti Yuli; Sari, Dewi Puspita (Philanthropy: Journal of Psychology, 2021)
AbstractThis study aims to determine the effect of strength use on employee engagement and performance. This study uses a quantitative explanatory research approach, with 173 subjects of credit division at BPR Restu Group Central Java and DIY. Processing data in this study using the SPSS 20.00 program for windows by looking at the descriptive test and path analysis. There are three hypotheses proposed in the study and the results of the analysis show that H1, H2, and H3 can be accepted. The analysis results show that the value of Sig.F 0.000